Impact of Septoplasty with High-Frequency Inferior Turbinate Reduction on Quality of Life - Ho, Minh Tri; Ho, Minh Duy; Tran, Ngoc Hong Nhung; Vo, Doan Minh Nhat; Hoang, Phuoc Minh; Nguyen, Luu Trinh; Le, Thanh Thai (Tạp chí Y Dược Huế, 2026)
Background: Nasal obstruction due to septal deviation and inferior turbinate hypertrophy is a common clinical complaint that significantly impairs quality of life. Surgical intervention, specifically septoplasty combined with inferior turbinate reduction, is a frequently performed procedure to alleviate these symptoms. This study aims to prospectively evaluate the efficacy of septoplasty with high-frequency radio-ablation of the inferior turbinates by assessing subjective and objective outcomes in patients with nasal obstruction. Methods: This prospective cohort study enrolled 34 patients at Hue University of Medicine and Pharmacy hospital with symptomatic nasal obstruction due to septal deviation and compensatory inferior turbinate hypertrophy. Preoperative evaluation included a detailed clinical history, nasal endoscopy, and computed tomography (CT) of the paranasal sinuses. Subjective outcomes were measured using the Nasal Obstruction Symptom Evaluation (NOSE) scale and the Sino-Nasal Outcome Test-22 (SNOT-22). Objective anatomical parameters, including the type of septal deviation (Mladina classification), the degree of turbinate hypertrophy (Friedman classification), and the angle of septal deviation, were assessed. All patients underwent endoscopic septoplasty and high-frequency radio-ablation of the inferior turbinates. Postoperative outcomes were evaluated at one month. Results: The study cohort consisted of 73.5% male and 26.5% female patients, with a mean age of 32.91 ± 13.256 years. The most common presenting symptom was nasal obstruction (70.6%). Preoperatively, the mean NOSE score was 61.32 ± 21.79, and the mean total SNOT-22 score was 30.88 ± 15.58. Postoperatively, at one month, the mean NOSE score significantly improved to 18.68 ± 10.39 (p < 0.01). Similarly, the mean total SNOT-22 score decreased to 14.56 ± 10.05 (p < 0.001). A statistically significant correlation was found between the severity of nasal obstruction on the NOSE scale and the type of septal deformity (p = 0.038), as well as the degree of contralateral turbinate hypertrophy (p = 0.010). Post-surgical endoscopic evaluation at one month revealed a straight septum in 76.5% of patients and a significant reduction in the size of the inferior turbinates in 97.1% (left) and 94.1% (right) of cases. Conclusion: The combination of septoplasty with high-frequency inferior turbinate reduction is a highly effective and safe procedure for treating nasal obstruction caused by septal deviation and turbinate hypertrophy. This intervention leads to a statistically significant improvement in patient-reported quality of life, as measured by the NOSE and SNOT-22 scores. The correlation between the severity of symptoms and specific anatomical deformities underscores the importance of a thorough preoperative evaluation. Keywords: Septoplasty, Inferior Turbinate Hypertrophy, High-Frequency Ablation, Nasal Obstruction, NOSE Score, SNOT-22, Quality of Life.